(untitled) (Global Journal of Management and Business Research, 2021)
This study examines the impact of the Internal Audit Control System on Operational Efficiency, a study of Akwa Ibom State Transport Company. The study was a survey design, and the population comprised all the 34 administrative staff of the AKTC finance, administrative and internal audit departments. A sample size of 31 staff was selected for the three chosen departments of the company for the study, and the sampling technique used was a single stage. The data for the study was purely primary data, where information was collected from the staff of the company via a questionnaire. The data obtained were analysed using simple regression analysis. The study’s findings revealed a significant relationship between internal audit control and increased revenue generation and net profit. The findings also revealed a statistically significant impact of the internal audit control system on operational efficiency. The relationship between the internal audit control system and further expansion was also significant. However, the work recommends that AKTC should set internal audit units for each branch across the country with internal audit personnel’s manning the unit and should rotate branches from time to time to ensure compliance.